Effects of micro and macro features on the thermal shock resistance of laminated Al2O3–MgO composites. Issue 7 (May 2020) - Liu, Changxia; Sun, Junlong; Gong, Feng; Li, Bin
Abstract: The thermal shock resistance (TSR) of laminated Al2 O3 –TiN–MgO/Al2 O3 –ZrB2 –MgO ceramic (LAMC) and Al2 O3 –TiN–MgO ceramic (ATMC) composites were investigated systematically by combining experimental data with stress intensity state theory. The microstructures and relative displacements before and after quenching, crack propagation, residual flexural strengths, and critical thermal shock temperature differences (Δ T c ) of the LAMC and ATMC composites were identified and investigated. The TSR of the LAMC composite was higher than that of the ATMC composite as determined by comparing micro and macro features of LAMC and ATMC composites. The effects of different experimental approaches on the TSR of LAMC and ATMC composites were analysed. The analysed values of Δ T c for LAMC and ATMC composites, acquired based on stress intensity state theory, were consistent with the experimental data of crack propagation.